CLINICAL RELEVANCE OF TUMOR-ASSOCIATED MACROPHAGES (TAMs) AND CARCINOMA-ASSOCIATED FIBROBLASTS (CAFs) IN ORAL SQUAMOUS CELL CARCINOMA (OSCC): IMMUNOHISTOCHEMICAL STUDY - Idoska Sanela; Popovik-Monevska Danica; Petrusevska Gordana; Popovski Vladimir; Grcev Aleksandar; Bozovic Suzana; Koneski Filip (My University, 2021)
Introduction: The factors, which influence or play a key role in tumor invasion and metastasis of the squamous cell carcinoma of the oral mucosa (OSCC), are subject of many scientific researches. Objectives: The aim of this study was to investigate the clinical relevance of OSCC infiltration with TAMs and CAFs. Materials and methods: Immunohistochemical analysis of both stromal/tumoral CD68+ TAMs and α-SMA positive CAFs was performed in paraffin–embedded tissue specimens from 23 OSCC patients and correlated with the clinical stage and degree of malignant cell differentiation. Results and conclusions: The presence of CAFs was not detected in the specimens of all 23 patients, but TAMs were found in all of them. Stromal myofibroblasts are heterogeneously detected in the OSCC, and the lowest density of CAFs is in the first clinical stage. There is a statistically significant correlation between clinical stage 1 and the degree of density of CAFs compared to other clinical stages (p=0.006474). There is a statistically significant difference between clinical stage 1 and other stages 2, 3 and 4, and the presence of TAMs in the tumor stroma (p<0.033179) and in the tumor nests also (p<0.033179). There is no statistically significant difference between the density of CAFs and the degree of differentiation of tumor cells, and also the degree of differentiation of tumor cells does not correlate with the expression of CD68+ TAMs neither in the tumor stroma (p=0.438807), nor in the tumor nest (p=0.9488644). Key words: Tumor microenvironment, carcinoma-associated fibroblasts, tumor-associated macrophages, oral squamous cell carcinoma.
Keywords: Tumor microenvironment, carcinoma-associated fibroblasts, tumor-associated macrophages, oral squamous cell carcinoma.